An Exploration of the Importance of Supporting Parents of Children with ASD; the Perspectives of Parents and Professionals - MacAlinney, Ciara (Trinity College (Dublin, Ireland). School of Education, 2021)
It is well established that parents of children diagnosed with ASD experience elevated anxiety and stress. This study aims to explore the importance of supporting parents of children with ASD and to determine the availability of supports from the perspectives of parents and EI professionals. The fundamental theories of supporting parents by EIS is based on providing services according to the bio-psycho-social model which recognises disability as an interaction between individual’s impairment and the environment. However, there is very limited research in the area of EI supports in Ireland. This study examined multiple aspects of supporting parents of children diagnosed with ASD; the role of the EI team, ASD, diagnosing ASD, the impact of the diagnosis on parents, parental stress, current supports for parents and the impact of these supports for parents. The researcher used a mixed-methods approach in which 54 parents took part in an online survey, and 4 EI professionals took part in semi-structured interviews. The collected data was analysed using thematic analyses resulting in 5 themes, which highlighted the importance of professionals recognising, valuing and supporting parents. This can significantly improve the quality of life for parents of children diagnosed with ASD when they feel supported through EIS and social activities in their community. A key finding is the insufficiency of current resource provisions. Among the key recommendations that have emerged from this study are; increased funding and recruitment for EI teams, the addition of counsellors to EI teams, and the creation of a specific parent support role to EI teams.
Keywords: Early Intervention; Education